Robust L2 - L∞ filtering for a class of dynamical systems with nonhomogeneous Markov jump process - Yin, Y.; Peng, S.; Fei, L.; Teo, Kok Lay (Taylor & Francis Ltd., 2015)
This paper investigates the problem of robust L2 - L∞ filtering for a class of dynamical systems with nonhomogeneous Markov jump process. The time-varying transition probabilities which evolve as a nonhomogeneous jump process are described by a polytope, and parameter-dependent and mode-dependent Lyapunov function is constructed for such system, and then a robust L2 -L8 filter is designed which guarantees that the resulting error dynamic system is robustly stochasticallystable and satisfies a prescribed L2 - L∞ performance index. A numerical example is given to illustrate the effectiveness of the developed techniques.